Pengembangan Kemampuan Bahasa Keaksaraan Awal Anak Usia 5-6 Tahun Melalui Media Multisensori - Nurjani, Yan Yan; Rahmah, Yuke Yunianita (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
This research is motivated by the situation of students at Al-Ikhlas Garut Kindergarten who still have not reached the expected level of success, this is due to several factors, including the drill learning method that is carried out not in accordance with the characteristics of early childhood as well as the needs of children who have not been fully facilitated. In this case, the researcher aims to develop early literacy language skills in Al-Ikhlas Kindergarten through multisensory media. Therefore, the question of this study is whether multisensory media can improve the language skills of early literacy of children aged 5-6 years at Al-Ikhlas Garut Kindergarten. This study uses a Classroom Action Research (PTK) design with 13 students aged 5-6 years. The research was carried out in 2 cycles, guided by the STPPA indicator of literacy language ability of children aged 5-6 years. Based on the results of the research through the application of multisensory media as a whole, it has been proven to be effective in improving and developing early literacy language skills of children aged 5-6 years. Judging from the percentage results, namely, cycle I BB (15.4%), MB (46.1%), BSH (38.5%), BSB (0%). Meanwhile, the second cycle is, BB (0%), MB (7.7%), BSH (61.5%), BSB (30.8%).  Keywords: Early Childhood; Early literacy language skills; Multisensory Media